Feed-in tariff scheme for promoting wind energy generation - Chanapan Kongnam (2018)
This paper proposes feed-in tariff scheme as investment incentive to promote wind energy generation under a regulated environment. The tariff design problem is to determine proper price premium that would be added to electricity purchasing rate when electricity generation is from wind energy. The problem was formulated as a mixed-integer nonlinear programming and solved for optimum capacity and price premium of each wind turbine model. The premium schemes are proposed to be fixed or time-varying, depending on generation capacity of a wind turbine. The impacts of implementing the premium schemes on generation capacity of different wind turbines, cost of subsidy, and generation profit are addressed. © 2009 IEEE.